High-Level Transgene Expression in Nonhuman Primate Liver with Novel Adeno-Associated Virus Serotypes Containing Self-Complementary Genomes - Gao, Guang-Ping (American Society for Microbiology, 2006)
Adeno-associated virus (AAV) vectors are being considered for in vivo applications of gene therapy in the treatment of a variety of disorders. This study evaluates the biology of second-generation vectors based on the novel serotypes AAV7 and AAV8 and containing self-complementary genomes in the nonhuman primate liver. Stable levels of transgene expression were achieved in cynomolgus macaques and suggest efficiencies at least 2 log higher than what could be achieved with AAV2 vectors using traditional single-stranded genomes. Analysis of DNAs from tissues revealed high levels of vector in the liver that appeared proportional to the relative amounts of transgene expression.